PERLINDUNGAN HUKUM BAGI PENUMPANG JASA ANGKUTAN ORANG DENGAN KENDARAAN BERMOTOR UMUM DALAM TRAYEK - Hana Nur Falinda; Arikha Saputra (Universitas Muhammadiyah Ponorogo, 2022)
The purpose of this research is to get a complete and clear picture of the problems that exist in society. The problem raised is how the legal protection of what factors affect Article 143 and its legal remedies. The writing method that underlies this research is a normative juridical research method with analytical descriptive nature. Legal protection for passengers from transportation as contained in Article 192 paragraph (1) of Law No. 22 of 2009 concerning Road Traffic and Transportation (UULLAJ), that public transportation companies are responsible for losses suffered by passengers who die or are injured as a result of transportation operations. , unless caused by an unavoidable or unavoidable event or by mistake. The form of responsibility can be in the form of compensation in the form of providing assistance or care and accident compensation. Some of the factors that cause traffic violations in Semarang Regency, namely the human factor, this is the lack of public understanding in maintaining traffic safety by following the rules in (UULLAJ) such as not wearing a standard helmet, not carrying a driving license (SIM) and STNK and not on the right route. Various ways of overcoming efforts have been carried out by the Semarang Regency Government and the police by using preemptive (educational), preventive (preventive) and repressive (law enforcement) methods. Meanwhile, from the Semarang Regency Transportation Agency, which acts as the Regency government. Semarang, which has attempted to take action against traffic violations such as carrying out roadworthy controls for motorized vehicles whose targets are goods vehicles, public transport vehicles and controlling the administrative requirements of public transport agreements.